High resolution computed tomography and chest radiography findings among interstitial lung disease patients - Pal, Anusmriti; Yadav, Manoj Kumar; Pant, Chiranjibi; Shrestha, Bishow Kumar (Journal of Chitwan Medical College, 2019)
Background: Interstitial lung disease (ILD) is a heterogeneous group of diffuse parenchymal lung diseases, characterized by restrictive physiology, impaired gas exchange, pulmonary inflammation and fibrosis. Chest radiograph (CXR) may appear normal during initial course of the disease and may show few abnormalities. High resolution computed tomography (HRCT) chest is a most accurate non-invasive, high spatial resolution descriptive imaging modality for evaluation of lung parenchyma. It assesses presence, location, type and characterization of ILD in appropriate clinical setting. Our aim was to study radiological patterns and its distribution in CXR and HRCT chest of ILD patients. Methods: This was an observational, single centered, cross-sectional study conducted at author’s place over the period of 6 months starting from January 2018 using convenient sampling method. Data analysis was done using students t-test for comparison of means and chi-square test for proportions. Results: A total of 30 suspected or diagnosed patients of ILD were enrolled in our study and patterns found on CXR were correlated with that on HRCT chest. The number of findings in HRCT chest for a patient was significantly higher than CXR (Median number: 4 verses 2, P<0.001), commonest reticular opacity 50% in CXR and 56.6% HRCT. One subject had normal CXR. Conclusion: HRCT was superior to CXR in detection of all basic patterns and their distribution associated with ILD as higher numbers of findings were detected by HRCT chest as compared to CXR. HRCT chest could characterize the abnormality and specify its location much more accurately.